On the significant impact of the moderate geomagnetic disturbance of March 2008 on the equatorial ionization anomaly region over Indian longitudes - Mridula, N.; Manju, G.; Pant, Tarun Kumar; Ravindran, Sudha; Jose, Lijo; Alex, S. (My University, 2011)
The response of the equatorial and lowâ€ latitude ionosphere plasmasphere system to the moderate geomagnetic disturbance of March 2008 is the subject of this paper. This study for the first time reports large plasmaspheric electron content modulation at equatorial and lowâ€ latitude regions over India during a moderate geomagnetic disturbance. This paper also presents, for the first time, five station tomograms encompassing the entire EIA region and unequivocally demonstrates the effectiveness of tomographic technique in investigating stormâ€ induced modulations of the equatorial ionization anomaly. The present study has been carried out using the total electron content values derived from GPS and Coherent Radio Beacon Experiment (CRABEX) data over Indian longitudes, ionosonde data at Trivandrum (8.5Â°N, 77Â°E) and Delhi (28Â°N, 78Â°E), and the geomagnetic field data from Trivandrum and Alibag.
Keywords: Geomagnetic disturbance; Equatorial ionization; Low latitude ionosphere; Plasmaspheric electron content; Tomographic technique; GPS; Coherent Radio Beacon Experiment; Trivandrum; Delhi; Alibag